Pengaruh Profitabilitas, Solvabilitas, Dan Rasio Aktivitas Terhadap Return Saham Dengan Nilai Perusahaan Sebagai Variabel Intervening Pada Perusahaan Consumer Goods Industry Yang Terdaftar Di Bei - Haryono Haryono; Aji Sukarno; Budi Santosa; Rizki Muti Agustiani (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
The purpose of this study was to determine and analyze the effect of Debt to Equity Ratio (DER), Earning Per Share (EPS), Price to Earnings to Growth (PEG), Return On Equity (ROE), and Total Assets Turnover (TATO) on stock returns through the firm value in the consumer goods industry companies for the period 2016-2020, and determine how much influence the Debt to Equity Ratio (DER), Earning Per Share (EPS), Price to Earnings to Growth (PEG), Return On Equity (ROE), and Total Assets Turnover (TATO) on stock returns through the firm value in the consumer goods industry companies for the 2016-2020 period. The data used in this study were obtained from www.idx.co.id and www.investing.com with a total of 120 data. Sampling was done by purposive sampling technique. The data analysis technique used is multiple linear regression analysis, hypothesis testing, and path analysis. The results showed that firm value was able to mediate the effect of Price to Earnings to Growth (PEG) and Total Assets Turnover (TATO) on stock returns, while firm value was unable to mediate the effect of Debt to Equity Ratio (DER), Earning Per Share (EPS), and Return On Equity (ROE) on stock returns.